KANK1 promotes breast cancer development by compromising Scribble-mediated Hippo activation - Shiny Shengzhen Guo; Zhiying Liu; Guan M. Wang; Zhiqi Sun; Kaikai Yu; James P. Fawcett; Reinhard Buettner; Bo Gao; Reinhard Fässler (Nature Communications)
Abstract KANK1 is expressed in epithelial cells and connects focal adhesions with the adjacent cortical microtubule stabilizing complex. Although KANK1 was shown to suppress cancer cell growth in vitro, TCGA database points to high KANK1 levels associated with poor prognosis in a wide spectrum of human malignancies. Here, we address this discrepancy and report that KANK1 promotes proliferation and survival of PyMT-transformed mammary tumor cells in vivo. Mechanistically, KANK1 localizes to the basal side of basement membrane (BM)-attached transformed luminal epithelial cells. When these cells lose the contact with the BM and disassemble integrin adhesions, KANK1 is found at cell-cell junctions where it competes with the polarity and tumor suppressor Scribble for NOS1AP binding, which curbs the ability of Scribble to promote Hippo pathway activity. The consequences are stabilization and nuclear accumulation of TAZ, growth and survival of tumor cells and elevated breast cancer development.